2016
DOI: 10.1016/j.phrp.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Rifampicin- and Isoniazid-Resistant Mycobacterium tuberculosis using TaqMan Allelic Discrimination

Abstract: ObjectivesMultidrug-resistant tuberculosis (MDR-TB) is a global problem that many countries are challenged with. Rapid and accurate detection of MDR-TB is critical for appropriate treatment and controlling of TB. The aim of the present study was to evaluate the TaqMan allelic discrimination without minor groove binder (MGB) as a rapid, efficient, and low-cost method for detection of drug resistant strains of Mycobacterium tuberculosis.MethodsA total of 112 M. tuberculosis isolates from cases with diagnosed TB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
2
3
1
Order By: Relevance
“…According to data from domestic and overseas research, the majority of ETH/PTH-resistant strains also show INH resistance. 10 , 14 , 15 In the present study, almost all ETH-resistant strains were also found to be resistant to both INH and RIF (96.4%), and the ETH-resistance rate in MDR-TB was 27.8%, which is consistent with our previous studies and similar data (20%–24.8%) from TB treatment institutions in China. 16–19…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…According to data from domestic and overseas research, the majority of ETH/PTH-resistant strains also show INH resistance. 10 , 14 , 15 In the present study, almost all ETH-resistant strains were also found to be resistant to both INH and RIF (96.4%), and the ETH-resistance rate in MDR-TB was 27.8%, which is consistent with our previous studies and similar data (20%–24.8%) from TB treatment institutions in China. 16–19…”
Section: Discussionsupporting
confidence: 92%
“…A recent study in South Korea found that only 23 (67%) of 34 PTH-resistant strains had an inhA mutation, while data from a study in Guangzhou, China indicates that, of 46 PTH-resistant strains, 43.2% had an inhA promoter (12 strains were c-15t and 4 strains t-8c), and 6.2% had a coding gene mutation (all were S94A). 10 , 21 The results of the present study show an inhA mutation rate in ETH-resistant strains (42.9%) similar to that in the study in China referenced above.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Four TaqMan probes, which could distinguish one-base mismatches, were used to detect genetic variation in the wild-type M. tuberculosis strain (H37Rv) in both rpoB and katG . All primers and probes used in this study were manufactured by Integrated DNA Technologies Inc. ( Table 1 ) [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%